Introducing second language acquisition - Saville-Troike, Muriel, 1936-; Barto, Karen, 1976- (Cambridge, United Kingdom : Cambridge University Press, 2017)
"Providing a solid foundation in second language acquisition, this book has become the leading introduction to the subject for students of linguistics, psychology and education, and trainee language teachers. Now in its third edition, the textbook offers comprehensive coverage of fundamental concepts, including second language acquisition (SLA) in adults and children, in formal and informal learning contexts, and in diverse socio-cultural settings, and takes an interdisciplinary approach, encouraging students to consider SLA from linguistic, psychological and social perspectives. Each chapter contains a list of key terms, a summary, and a range of graded exercises suitable for self-testing and class discussion. The third edition has been revised throughout, and features new material on the practical aspects of teaching language, along with updated online resources, including new classroom activities to accompany each chapter, as well as updated references and further reading suggestions"--
Machine generated contents note: 1. Introducing second language acquisition; 2. Foundations of second language acquisition; 3. The linguistics of second language acquisition; 4. The psychology of second language acquisition; 5. Social contexts of second language acquisition; 6. Acquiring knowledge for L2 use; 7. L2 learning and teaching.
Includes bibliographical references (pages 219-229) and index.
Keywords: Second language acquisition; LANGUAGE ARTS & DISCIPLINES / Linguistics / General